2022
DOI: 10.1029/2022ja030523
|View full text |Cite
|
Sign up to set email alerts
|

Mass Density Inferred From Toroidal Wave Frequencies and Energization of Low‐Energy Helium Ions During H‐Band EMIC Wave Interval

Abstract: Van Allen Probe A observed strongly enhanced hydrogen (H+) band electromagnetic ion cyclotron (EMIC) waves lasting >6 hr without helium (He+) band EMIC wave activity outside the plasmasphere on 23 February 2014. During the H‐band EMIC wave interval, multiharmonic toroidal waves were detected by the spacecraft. We estimated the local mass density using the observed toroidal wave frequencies and background electron number density. It was found that the average ion mass is close to 1. This indicates that the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…Our numerical analysis provides that the behavior of cold ions energized by EMIC waves occurs in two steps. In the first step, EMIC waves are excited in the strong H-band and weak He-band in the early stage of the simulation (Ω H t = 0-150) and energize cold H + and He + ions mostly in the direction perpendicular to the background magnetic field, which is consistent with recent observations in the inner magnetosphere (Kim et al, 2022). Our simulations show that the cold particle energization in this step is mainly due to the bulk motions of cold particles.…”
Section: Comparison With Previous Satellite Observations In the Inner...supporting
confidence: 87%
See 3 more Smart Citations
“…Our numerical analysis provides that the behavior of cold ions energized by EMIC waves occurs in two steps. In the first step, EMIC waves are excited in the strong H-band and weak He-band in the early stage of the simulation (Ω H t = 0-150) and energize cold H + and He + ions mostly in the direction perpendicular to the background magnetic field, which is consistent with recent observations in the inner magnetosphere (Kim et al, 2022). Our simulations show that the cold particle energization in this step is mainly due to the bulk motions of cold particles.…”
Section: Comparison With Previous Satellite Observations In the Inner...supporting
confidence: 87%
“…Kim et al. (2022) also observed that H‐band EMIC waves can energize cold protons and He + ions in the perpendicular direction and that the helium ions are more energized than the protons by the H‐band wave.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, a close correlation between the occurrence of EMIC waves and cold He + ions heating was found in previous observations (K H Kim et al., 2021; Lee et al., 2021; D Young et al., 1981; J. C. Zhang et al., 2011). The cold He + ions can be energized by EMIC waves up to suprathermal energies (tens of eV to a few hundred eV) in the perpendicular direction to the background magnetic field (K. H. Kim et al., 2022; Omidi et al., 2010; Shi et al., 2020; Yuan et al., 2016). The energy of the cold He + ions is much lower than the typical minimum resonant energy of EMIC waves, thus, the energy transfer between cold He + ions and EMIC waves should also be a non‐resonant interaction mechanism, which has been explored in theory and numerical simulation (Berchem & Gendrin, 1985; Bortnik et al., 2010; Mauk, 1982; Omura et al., 1985).…”
Section: Introductionmentioning
confidence: 99%